The South Korean case of deploying rural broadband via fiber networks by implementing universal service obligation and public-private partnership based project. (April 2023) - Lee, Hyeongjik; Jeong, Seonkoo; Lee, Kwanghee
Abstract: Despite broadband being essential infrastructure for conducting basic socio-economic activities and reducing inequality and the digital divide, expanding broadband coverage in rural areas remains a significant challenge in many countries due to high deployment costs. South Korea, a developed country in terms of fixed broadband penetration, implemented two policies for rural broadband via fiber access networks simultaneously during the COVID-19 pandemic. One is the universal broadband service at 100 Mbps speed introduced in 2020, and the other is the rural broadband project in terms of a public-private partnership (PPP) that proceeded from August 2020 to 2022. While both policies contribute to reducing the broadband gap between the urban and the rural in the country, it is still important to find the optimal cost-effective combination of the plural rural policies as much as possible from the cost perspective. Accordingly, this study proposes an investment cost estimation model for deploying rural broadband via fiber networks in South Korea and evaluates whether implementing two rural broadband policies in the country is cost-effective. The proposed model is designed according to the bottom-up approach, which involves building an efficient network with the latest technologies; thus, it gives a more accurate and reliable estimation of the investment cost of building rural broadband in the South Korean territory. The significant findings of this study are twofold. First, the PPP-based project could make the participating internet service providers (ISPs) deploy broadband at a cost-effective level, similar or lower to the universal service, and then recover the investment cost per building within a reasonable period. Thus, the result implies that governments need to consider the PPP-based project as an effective measure to deploy rural broadband, in addition to the introduction of universal service. Implementing multiple broadband policies to expand rural broadband coverage could be a reasonable and practical approach to improving broadband availability. Second, the governments still needs to make efforts to solve the complicated difficulties in rural areas in South Korea where rural-related broadband policies are still challenging to implement. This study confirmed that in some regions, the PPP-based project was still inferior to universal service in terms of average investment cost. In contrast, universal service had significant constraints to providing broadband because of the end-users cost burden, resulting in low broadband adoption. Therefore, the government needs to consider some measures to increase broadband availability and broadband adoption, such as widening the rural areas under the jurisdiction of participating ISPs, decreasing the proportion of participating ISPs bearing the investment cost of deploying broadband, and improving the cost burden of the end-users of universal service in some limited areas. Highlights: Universal service and rural broadband project (PPP) examined on the basis of investment cost. Rural South Korea divided into six geo-types with 127 areas as samples to represent each type. Fiber to the home and fiber to the distribution point selected as technologies. Regardless of technology, the investment cost can be recovered from monthly subscriptions. Rural broadband project is an effective measure to deploy rural broadband, in addition to the introduction of universal service.